Estimasi Biaya Non Produksi Kegiatan Usaha Tani Padi di Desa Padaelo Kecamatan Mattiro Bulu Kabupaten Pinrang - Jamil Hasyim Kahar; Nurhapsa Nurhapsa; Arman Arman (Jurnal Agribis, 2025)
The Bugis community culture related to farming involves six major ceremonies associated with rice cultivation, all of which are deeply rooted in their faith and belief in God. These traditions include rituals such as mappammula, mappalili, maddoja bine, mangngeppi ase, maddumpu, and mappadendang. The purpose of this study is to understand the post-harvest traditions practiced by farmers and to identify the non-production costs incurred by rice farmers from preparation to post-harvest. The study concluded that the traditions and non-production expenditures by farmers include: mappalili with an average cost of one hundred forty one, six hundred sixty seven, maddoja bine with an average cost of five thousand, mangngeppi ase with an average cost of Rp. Twenty two thousand five hundred, maddumpu ase with an average cost of eighteen thousand five hundred, mappammula with an average cost of two hundred nine thousand three hundred thirty four, and mappadendang with an average cost of seventy fife thousand. The usefulness of this research is that researchers can directly apply the knowledge gained in college to farmers, helping them to develop knowledge, particularly in the field of agriculture and non-production activities in rice farming.